1988
DOI: 10.14492/hokmj/1381517804
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of convolution equations in $K^{'}_{M}$

Abstract: Net S be a convolution operator in the space K_{M}' , M is an increasing continuous function, of distributions in R^{n} growing not faster than e^{M(kx)} for some positive integer k. We give necessary and sufficient condition on S to have S*K_{M}'=K_{M}' , then we use this condition to get necessary and sufficient conditions for solvability of systems of convolution equations in K_{M}' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…More specifically, the anatase modes (A 1g + B 1g + 3E g ) appear at 143, 196, 396, 514, and 638 cm −1 , [32] while the rutile modes (A 1g + E g ) are observed at 446 and 608 cm −1 . [30] By increasing the annealing temperature of pure TiO 2 and W-TiO 2 , we observed the shift of the peak E g (1) (144 cm −1 ) toward lower wavenumbers and the reduction of its intensity. While there is a broadening and shifting toward higher wavenumbers by increasing the percentage of doping.…”
Section: Ramanmentioning
confidence: 76%
See 1 more Smart Citation
“…More specifically, the anatase modes (A 1g + B 1g + 3E g ) appear at 143, 196, 396, 514, and 638 cm −1 , [32] while the rutile modes (A 1g + E g ) are observed at 446 and 608 cm −1 . [30] By increasing the annealing temperature of pure TiO 2 and W-TiO 2 , we observed the shift of the peak E g (1) (144 cm −1 ) toward lower wavenumbers and the reduction of its intensity. While there is a broadening and shifting toward higher wavenumbers by increasing the percentage of doping.…”
Section: Ramanmentioning
confidence: 76%
“…This is in good agreement with other studies that reported the absence of WO 3 phase below 20 wt% of tungsten. [30,31]…”
Section: Xrdmentioning
confidence: 99%
“…Finite Element Analysis: The commercially available finite element analysis package ABAQUS [71] for understanding the mechanics of the stimulus-responsive shape transformation behavior of Kirigami-cut bilayers was used. Following an already established protocol, [40,43,[72][73][74] the mismatch strain-driven bilayer morphing was modeled as an equivalent thermal expansion problem where one layer expands with respect to the other in response to a hypothetical temperature. In our computations, 4-node general purpose shell elements with throughthickness variation in material properties (the element size was determined from separate mesh refinement studies) and appropriate boundary conditions were used.…”
Section: Methodsmentioning
confidence: 99%
“…Both chalcones and their heterocyclic derivatives had proven their potential in numerous demanding pharmacological activities such as antimicrobial [1,2], antimalrial [3], anti-inflammatory [4][5][6], antitumor [7,8], antifungal [9], and antioxidant activity [10][11][12][13]. On the other hand, many researchers had reported chalcones containing sulfur either as a part of heteroaryl ring (thiophene) or as a side chain (thiomethyl group) for further enhancement of their biological activities [14][15][16]. Furthermore, it had been reported that both quinolin-2ones and fused pyrimidine heterocycles represent active classes of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%